Innovation and Vulnerability: Balancing Risk and Reward in Small Business Ventures - Rani Santika; Rafi Farizki (Publikasi Indonesia, 2025)
This chapter explores the dynamic relationship between innovation and risk management in small business ventures, emphasizing the need to balance technological advancements with effective safeguards to ensure long-term resilience. As small businesses increasingly adopt digital tools and innovative practices in the context of Industry 5.0, they encounter both growth opportunities and heightened vulnerabilities, particularly in cybersecurity, financial stability, and operational continuity. Through case studies and empirical findings, this chapter demonstrates how phased implementation, risk assessment, and resilience-building technologies, such as data analytics and cybersecurity measures, can help mitigate risks associated with innovation. The chapter underscores the importance of a balanced approach, where strategic innovation aligns with robust risk management, empowering small businesses to achieve sustainable growth and competitive advantage in a rapidly evolving market.